ANALISIS PENERIMAAN SISTEM E-LEARNING MENGGUNAKAN TECHNOLOGY ACCEPTANCE MODEL (TAM) - Surya Ade Saputera; Ema Utami; M. Rudyanto Arief (Informasi Interaktif, 2017)
E-learning is a new way in teaching and learning process that uses electronic media especially internet as a learning system .. E-learning University of Muhammadiyah Bengkulu is an online learning for students of Muhammadiyah University of Bengkulu. This study aims to analyze the level of user acceptance of the use of E-learning system using TAM method through SEM analysis and what recommendations can be given as input to the campus of the elearning system used. The research method used is descriptive analysis. Data analysis is done by SEM (Structural Equation Modeling) with AMOS (Analysis of Moment Structure) software. The results showed the level of user acceptance in using the UMB Elearning is on a high scale but at a low level that is an average of below 3 (1-4 scale). Factors influencing user acceptance in using E-learning System of University of Muhammadiyah Bengkulu by using Technology Acceptance Model (TAM) is Perceived Ease Of Use (PEOU) or ease of use and Attitude Toward Using (ATU) or user attitude in using E-learning system. From these results resulted in improved recommendations on the application of Elearning through User Interface approach which is expected to increase the usefulness of the application.Keywords: E-learning,  Technology Acceptance Model (TAM), SEM